2014
DOI: 10.1371/journal.pone.0099883
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Receptor REV-ERBα Regulates Fabp7 and Modulates Adult Hippocampal Neurogenesis

Abstract: The function of the nuclear receptor Rev-erbα (Nr1d1) in the brain is, apart from its role in the circadian clock mechanism, unknown. Therefore, we compared gene expression profiles in the brain between wild-type and Rev-erbα knock-out (KO) animals. We identified fatty acid binding protein 7 (Fabp7, Blbp) as a direct target of repression by REV-ERBα. Loss of Rev-erbα manifested in memory and mood related behavioral phenotypes and led to overexpression of Fabp7 in various brain areas including the subgranular z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 66 publications
8
70
0
Order By: Relevance
“…We previously observed that Nr3c1 mRNA expression is downregulated in the suprachiasmatic nuclei (SCN) of Rev-erbα −/− mice compared to wild-type animals (Schnell et al, 2014). This prompted us to test a potential relationship between REV-ERBα and GR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously observed that Nr3c1 mRNA expression is downregulated in the suprachiasmatic nuclei (SCN) of Rev-erbα −/− mice compared to wild-type animals (Schnell et al, 2014). This prompted us to test a potential relationship between REV-ERBα and GR.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection and luciferase reporter assays were performed with NIH3T3 cells according to Schnell et al (2014). The Bmal1 promoter region cloned into pGL3 were used as positive controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FABP5- and FABP7-deficient mice have a high level of AEA and NAEs in the brain and show analgesia in inflammatory pain models [28]. FABP7 mRNA expression is known to be regulated by REV-ERBα, and FABP7 is highly expressed in KO mice [29]. Therefore, the excessive expression of FABP7 may have contributed to causing the mechanical nociceptive sensitivity change in the KO mice in the present study.…”
Section: Discussionmentioning
confidence: 76%
“…To uncover temporal patterns of mRNA abundance, we performed k-means clustering on genes displaying statistically significant temporal expression, defined as follows: to identify genes displaying a statistically significant effect over time, we used a likelihood ratio test implemented by sleuth version 0.29.0 (57), comparing a 29 full model with a parameter for each time point plus a batch effect (i.e. t=[0, 3,6,12,18,24,27,30,36,42,48,54,60,66,72, 78] plus a batch effect) versus a null model with no time effect (i.e. only a batch effect).…”
Section: Clustering Of Mrna Profilesmentioning
confidence: 99%